Project on Human Development in Chicago Neighborhoods (PHDCN): Conflict Tactics for Parent and Child, Wave 1, 1994-1997 - Earls, Felton J. ([Verlag nicht ermittelbar], 2005)
The Project on Human Development in Chicago Neighborhoods (PHDCN) was a large-scale, interdisciplinary study of how families, schools, and neighborhoods affect child and adolescent development. One component of the PHDCN was the Longitudinal Cohort Study, which was a series of coordinated longitudinal studies that followed over 6,000 randomly selected children, adolescents, and young adults, and their primary caregivers over time to examine the changing circumstances of their lives, as well as the personal characteristics, that might lead them toward or away from a variety of antisocial behaviors. Numerous measures were administered to respondents to gauge various aspects of human development, including individual differences, as well as family, peer, and school influences. One such measure was the Conflict Tactics Scale for Parent and Child (CTSS). The CTSS, administered to the primary caregiver (PC) of subjects belonging to Cohorts 3 to 15, measured psychological and physical maltreatment and neglect of children by their PC, as well as nonviolent modes of discipline. The CTSS also measured the extent to which a PC carried out specific acts of physical and psychological aggression, regardless of whether the child was injured.